Penerapan Metode Reading Guide untuk Meningkatkan Kemampuan Membaca Siswa Kelas II Madrasah Ibtidaiyah Swasta Nurul Ittihad Kota Jambi - Kuratul Aini; Saidah Ahmad (STIKes Ibnu Sina Ajibarang, 2025)
Grade II students at Madrasah Ibtidaiyah Nurul Ittihad in Jambi City are struggling with reading comprehension, which is affecting their ability to understand the content of reading materials, accurately interpret information, and answer questions related to the text. To help kids become better readers, educators have developed the Reading Guidance Approach. The research here follows the four-step model proposed by Kemmis and McTaggart: preparation, execution, evaluation, and revision. The purpose of this research is to help second graders studying Indonesian at Nurul Ittihad Private Madrasah Ibtidaiyah in Jambi City enhance their reading comprehension abilities. Data was gathered via observation, interviews, assessments, and recording over the course of two cycles of three sessions each. The research found that between cycles I and II, instructor activities rose by 17% and student activities increased by 8%. From 28% in the pre-cycle, 71% in Cycle I, and 89% in Cycle II, the results of the learning completeness test indicated a steady rise. According to these findings, second graders at Nurul Ittihad Private Elementary School in Jambi City who are studying Indonesian benefit from the reading guidance strategy in terms of their reading comprehension abilities.